Panvesco’s Chairman Quits - Joseph, Terry (Trinidad Express)
Clary Benn tendered his resignation as chairman of the Pan Trinbago Investment Company (Panvesco) and was followed by two other board members, at a specially convened meeting of the Board.
Keywords: Steel bands (Music) -- Administration -- Trinidad and Tobago; Resignation; Steel bands (Music) -- Trinidad and Tobago